An Algorithm to Predict Life-Threatening Complications using Heart Rate Variability and the Circadian Heart Rate Difference with a Special Interest on Covid-19, Sudep Children with Congenital Heart Disease and Obesity - Buchhorn, Reiner (British Journal of Healthcare and Medical Research, 2020)
Corona virus disease (COVID-19) has been declared as a pandemic by the WHO with a global mortality rate of about 3.4%. More recently the neuroinvasive potential of SARS-CoV2 was emphasized as a potential cause for respiratory failure. Such pathophysiology has been investigated in sudden unexplained death in epilepsy (SUDEP) including functional neuroimaging that demonstrates alterations to networks involved in central autonomic and respiratory control located in the brainstem. For risk stratification in these patients, one method may be heart rate and heart rate variability (HRV) monitoring. Method: For a better understanding, we compare HRV monitoring in two cases; 1.) Twenty Holter ECGs of a boy with generalized tonic-clonic seizures up to his dead at the age of 10.5 years with special interest on an acute respiratory failure at the age of 5.4 years. 2.) Thirty one Holter ECGs of a 58-year old pediatric cardiologist who survived an infection with COVID-19. During his disease 24-hour Holter electrocardiography (ECG) was performed continuously over 10 days. Moreover, 24-hour Holter ECGs from the last 10 years were available. The derived algorithm that depends on the global heart rate variability and circadian heart rate difference was proofed in 151 healthy children, 26 children with a fatal outcome or transplantation, 151 patients with operated congenital heart disease, 130 obese children and healthy adult data from literature. Results: In both cases we observe a decline of the global heart rate variability SDNN together with a loss of the circadian heart rate difference. The derived algorithm differentiate healthy children from children with a fatal outcome. The algorithm identify 7.3% of 151 patients with operated congenital heart disease and 5.4% of children with obesity as candidates for COVID-19 complications. Conclusions: A sudden decline of HRV together with a loss of the circadian heart rate difference may indicate a life-threatening complication in critical illness.